Heutagogy approach in 21st century teaching and learning : practices and challenges in Malaysian higher education - Tiew, Chia Chun; Ng, Melissa Lee Yen Abdullah (Penerbit Universiti Kebangsaan Malaysia, 2021)
Heutagogy was first introduced by Steward Hase and Chris Kenyon in year 2000. It is a novel teaching and learning approach being implemented at Malaysian higher education institutions (HEIs), as a transformation initiative to improve the quality of education and to produce graduates who could meet the demands of the 21st century workforce. However, the extend of heutagogy principles being adopted and the challenges faced whilst implementing this new approach remains unclear. This study aims to fill in the knowledge gaps by conducting critical systematic reviews on the practices and challenges of heutagogy approach in teaching and learning at Malaysian HEIs. Research articles and policy papers on the practices of heutagogy approach in Malaysian higher education context were accessed through open-source and subscription databases. The results of systematic reviews found that four principles of heutagogy approach namely learner-centred, double loop learning, non-linear learning approach and a focus on skills development were being practiced at the local institutions. Nevertheless, the study also discovered several challenges, including lecturer, student, and environmental factors, that hinder the implementation of this new teaching and learning approach. The implications of the research findings were discussed in this paper.